2022
DOI: 10.3390/healthcare10020227
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Medical Doctors’ Work-Family Balance at German University Clinics

Abstract: The measures taken to cope with the COVID-19 pandemic by governments worldwide have vast consequences on all areas of life. To assess the impact of the COVID-19 pandemic on long-term career development, we evaluated the work-family balance of medical doctors at nine German university clinics. The results indicate a severely disturbed work-family balance, which was mostly due to insufficient childcare, based on restrictions in school operations and childcare. Despite the newly created emergency childcare option… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The COVID-19 pandemic also changed the overall work organization and arrangements, accelerating and disrupting various trends in the work area [ 17 ]. In particular, many schools and workplaces were closed during the lockdown, so stationary work was changed to remote online, and working parents were forced to divide their time between caring for children and teleworking [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Experts assumed the transition to telework was one of the essential issues for occupational health during the COVID-19 pandemic [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The COVID-19 pandemic also changed the overall work organization and arrangements, accelerating and disrupting various trends in the work area [ 17 ]. In particular, many schools and workplaces were closed during the lockdown, so stationary work was changed to remote online, and working parents were forced to divide their time between caring for children and teleworking [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Experts assumed the transition to telework was one of the essential issues for occupational health during the COVID-19 pandemic [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most sensitive groups for high WFC and FWC was parents of minor children [ 22 , 23 , 24 ]. For example, a disturbed work-family balance was found among German medical doctors due to insufficient childcare when schools and preschools were closed during the pandemic [ 19 ]. The study among Portuguese-employed parents showed that, dependent on the stationary or online type of work, diverse experiences were reported during the lockdown [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations